A Prospective Study of Male Depression, Psychotropic Medication Use, and Fecundability. Issue 1 (February 2022) - Yland, Jennifer J.; McKinnon, Craig J.; Hatch, Elizabeth E.; Eisenberg, Michael L.; Nillni, Yael I.; Rothman, Kenneth J.; Wise, Lauren A.
We examined the associations of male depression and psychotropic medication use with fecundability in a North American preconception cohort study (2013–2020). Men aged ≥21 years completed a baseline questionnaire with questions on history of diagnosed depression, the Major Depression Inventory (MDI), and psychotropic medication use. Pregnancy status was updated via bimonthly female follow-up questionnaires until pregnancy or 12 menstrual cycles, whichever occurred first. Analyses were restricted to 2, 398 couples attempting conception for ≤6 menstrual cycles at entry. We fit proportional probabilities models to estimate fecundability ratios (FRs) and 95% confidence intervals (CIs), adjusting for age (male and female), education, (male and female), race/ethnicity, physical activity, alcohol intake, body mass index, smoking, and having previously impregnated a partner. Nearly 12% of participants reported a depression diagnosis; 90.6% had low depressive symptoms (MDI <20), 3.5% had mild symptoms (MDI: 20–24), 2.7% had moderate symptoms (MDI: 25–29), and 3.3% had severe symptoms (MDI: ≥30). A total of 8.8% of participants reported current use of psychotropic medications. History of depression was associated with slightly reduced fecundability, although this result was also reasonably compatible with chance (FR = 0.89; 95% CI: [0.76, 1.04]). FRs for mild, moderate, and severe compared with low depressive symptoms were 0.89 (95% CI: [0.66, 1.21]), 0.90 (95% CI: [0.62, 1.31]), and 0.88 (95% CI: [0.65, 1.20]), respectively. This indicates little evidence of a dose–response relationship for depressive symptoms with fecundability, although estimates were imprecise. Current psychotropic medication use mediated 44% of the association between depressive symptoms and fecundability.